2017
DOI: 10.1016/j.cej.2016.09.131
|View full text |Cite
|
Sign up to set email alerts
|

A green method to prepare nanosilica modified graphene oxide to inhibit nanoparticles re-aggregation during melt processing

Abstract: A graphene oxide-silica nanohybrid (GOS), self-assembled into a lasagna-like structure, was prepared in water and used as a filler for the melt preparation of polyamide 6 (PA6)-based nanocomposites. For sake of comparison, PA6-based materials were prepared under the same processing conditions by adding GO only or a physical mixture of GO and silica (GO+S). All the materials were characterized from a morphological, spectroscopic, thermal, dynamic-mechanical (DMA) and mechanical point of view. For all the nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…That band's intensity varies with the system's aromaticity degree and the plasmon p-p* peak's intensity, between approximately 291-294 eV. The band at approximately 285.2 eV is attributed to the C-H bond from the aliphatic structure, related to hexagonal lattice defects (sp 3 [29]. From the XPS spectra, it can also be concluded that the highest percentage of C-O groups was achieved by CNT/O sample ($14% against $7% of pristine CNT) and for O-C 5 O groups was achieved by CNT/40 sample ($4.6% against $1.9% of pristine CNT), indicating that the plasma treatment at 40 W promotes the highest increase in oxygen functional groups.…”
Section: Characterization Of Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…That band's intensity varies with the system's aromaticity degree and the plasmon p-p* peak's intensity, between approximately 291-294 eV. The band at approximately 285.2 eV is attributed to the C-H bond from the aliphatic structure, related to hexagonal lattice defects (sp 3 [29]. From the XPS spectra, it can also be concluded that the highest percentage of C-O groups was achieved by CNT/O sample ($14% against $7% of pristine CNT) and for O-C 5 O groups was achieved by CNT/40 sample ($4.6% against $1.9% of pristine CNT), indicating that the plasma treatment at 40 W promotes the highest increase in oxygen functional groups.…”
Section: Characterization Of Cntsmentioning
confidence: 99%
“…Besides, the CNTs' characteristic chemical inertia impairs the adhesion to the matrix and therefore, a good tension transfers . The interfacial interaction between the matrix and the nanoparticles, which is indicated by an interphase region , can be improved with chemical or physical functionalization . The chemical functionalization, which consists of inserting functional groups onto the surface of nanoparticles, can be done through a plasma process.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased durability of these materials has raised strong concerns about the large accumulation of plastic waste in the environment [12]. Thus, the development of cleaner processes associated with the interest in environmentally friendly materials has been the focus of research around the world [13][14][15][16][17]. In this context, the addition of natural fillers (natural fibers, cellulose nanocrystals, and nanofibrillated cellulose) in the polymers has been a way to prepare ecofriendly composites with improved properties, minimizing the problem in relation to the residue accumulation [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…PointProbe Plus Silicon‐SPM‐probes were used with Al backside reflex coating, at a resonance frequency of ≈300 kHz and tip apical diameter of ≈10 nm. All the scans were executed at room temperature under N 2 atmosphere …”
Section: Methodsmentioning
confidence: 99%